Nutritional guidelines for athletic performance : the training table - Taylor, Lemuel W. (Boca Raton : CRC Press, 2012)
"Preface The idea and origination of this project came during a phone conversation with Dr. Ira Wolinsky, who read a previous book chapter that I had authored. After a couple more conversations and email exchanges, the idea for this book developed. The concept of the "Training Table" became the primary interest and direction of this book for various reasons. This practice known as the training table, which is defined as a "table" where athletes in a training program eat planned meals to help in their conditioning/training, leads ultimately to improved adaptation and enhanced performance. Even though many factors contribute to athletic performance, the role of proper nutrition cannot be emphasized enough. The importance of proper daily nutrition has several implications on overall health and proper homeostatic functioning of the body, but that can be said for any person, whether sedentary or an elite-level athlete. We do know that, when an individual goes from a sedentary to an active lifestyle, their daily nutrient needs change. If we extrapolate that to an elite athlete who is training a minimum of 15-20 hours per week, but in some cases as many as 40-60 hours per week, these nutrient requirements grow in proportion to this level of activity. Knowing this, it is vital for athletes, and for the individuals who train these athletes, to know the proper nutritional requirements that would be appropriate for their individual sport, body size, gender, goals, etc. This book addresses these needs for athletes on a comprehensive basis, from a training table perspective, and provides practical recommendations along the way to include the most signifi cant parts of a training table"--Provided by publisher.
The Role of the Training Table / Michael D. Roberts and Lemuel W. Taylor -- Energy Demands: Sedentary versus Active Individuals / Julie Kresta -- Energy Demands for Endurance Athletes / Ron Mendel -- Energy Demands for Strength-Power Athletes / Chris N. Poole and Colin D. Wilborn -- Meal Planning for Athletes / Amanda Carlson-Phillips -- Protein Needs of Athletes / Kristin Dugan and Colin D. Wilborn -- Carbohydrate Needs of Athletes / Christopher J. Rasmussen -- Fat Needs of Athletes / Jonathan M. Oliver, Michelle A. Mardock, and Justin P. Dobson -- Micronutrient Needs of Athletes / Fanny Dufour and Lemuel W. Taylor -- Fluid Needs of Athletes / Chad Kerksick -- Calorie Needs for Improving Body Composition / Vincent J. Dalbo and Michael D. Roberts -- Calorie Needs for Inducing Muscle Hypertrophy / Michael D. Roberts -- Nutrient Timing for Optimal Adaptation and Recovery / Brian D. Shelmadine, Paul M. La Bounty, and Kara A. Sample -- Carbohydrates: What We Know about Low versus High Levels for Athletes / Abbie E. Smith, Jose Antonio, and David H. Fukuda -- Nutrition for the Aging Athlete / Thomas W. Buford, Matthew B. Cooke, and Jean L. Gutierrez.
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Athletes -- Nutrition; Athletes -- Nutrition -- Requirements; Sports -- Physiological aspects; Electronic books